(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2023)
The pervasiveness of digital technologies is resulting in myriad problems that must be constantly dealt with in journalism education. Although the problems posed by digital storytelling in journalism have been recorded, there are no significant solutions sought for developing economies. The study aims to develop a model of training for digital storytelling in journalism applicable to developing economies and struggling higher education institutions A qualitative integrative literature review of journal articles was conducted to identify and synthesise recurrent themes indicating the nature of the challenges faced. Most reiterated are inadequate new media and visualisation skills among both students and faculty and limited research on the understanding of visual knowledge representations, challenges of upholding journalism ethics amid information saturation, failure to adapt curricula to the rapid change in digital spaces, and access. The model proposes using less expensive hardware tools available to students such as laptops, smartphones and freely available software to compose digital stories and edit the content to fit multiple channels. The model provides a guide for imparting basic digital storytelling skills in resource-constrained environments and adds to the body of knowledge in innovative digital storytelling in journalism. Importantly, the precipitous speed at which journalism is conducted and transformed requires innovative approaches to keep pace with the multimedia skills required.